A Critical Approach of the European Funds Absorbtion for the 2007-2013 Programming Period: Case Study - Regional Operational Programme of Romania - Dana Bako; Stefana Varvari (CES Working Papers, 2015)
For Romania, 2015 represents the year in which new programming documents are enacted, among which the Regional Operational Programme is the one that focusses on the harmonious development of the regions in terms of GDP/inhabitant and number of new jobs created. During the 2007-2013 period, 19% of the total EU contribution of EUR 19,667 million were allocated for this programme and about a third of the total allocation for 2014-2020 is provided for it. This shows that regional development was and is still considered one of the main objectives, after the improvement of the transport and environment infrastructure. In this context, the authors analyse, in a comparative manner, the results obtained on each axis and by each region during the 2007-2015 time-span, through the projects financed under the Regional Operational Programme 2007-2013 of Romania, trying to identify the main problems and bottlenecks and the way they were dealt with during these years, as well as the changes envisaged for the new ROP 2014-2020. For this analysis the monitoring and the evaluation reports were taken into consideration.
Keywords: O18; R58; 330; regional operational programme; regional development policy; European Regional Development Fund